Avaliação da eletrocoagulação e otimização de processo microbiológico de tratamento de efluente de uma indústria de cosméticos - Schneider, Jaine (2022)
The increasing consumption of the most diverse types of cosmetics also increases the generation of solid and liquid waste in cosmetic industries. Thus, the search for alternative, less expensive and effective treatments to remove contaminants such as organic load, surfactants and oils and grease from the liquid effluent is also increasing, since the generating companies are responsible for their waste and are subject to fines and lawsuits if they do not meet the standards required by environmental agencies. The electrocoagulation (EC) comes as an alternative for the treatment of effluents aiming at the removal of contaminants and presenting several advantages, among them the low operating cost, since it does not require the insertion of chemicals in the process, thus, the production of coagulant agent in situ and low production of sludge. In this study, the electrocoagulation combined with the activated sludge process was investigated for the removal of pollutants from an effluent of a cosmetics industry compared to the treatment process already adopted by the industry - coagulation-flocculation (EC). The variables of the CE were the construction material of the electrodes (iron and aluminum), the pH, the electrolysis time and the applied voltage. From the results it was possible to verify that in terms of COD removal the reduction of COD was in the order of 62% and 74% for aluminum and iron, respectively, in the optimal condition of pH 7 and voltage 20V. The activated sludge technology was applied to the effluent treated by electrocoagulation and the real effectiveness of the treatment by different commercial bacteria kits was evaluated when compared to coagulation-flocculation. The best results were for the treatment of CE with iron and aluminum, on the order of 98.7% and 94.9%, respectively, after 10 days of microbiological treatment when compared to the FC, which obtained 94.9% of COD removal after 14 days of microbiological treatment as post treatment, so the results were satisfactory because it meets the established parameters in less time with the use of commercial kits of bacteria.